Radio-Ulnar Synostosis Complicating Partial Mid-Diaphyseal Ulnar Ostectomy in Growing Dogs - MacPherson, G. C.; Johnson, K. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Radio-ulnar synostosis developed in two dogs that had partial mid-diaphyseal ulnar ostectomies performed to correct asynchronous growth of the radius and ulna. The synostosis was apparently painful and caused lameness in one dog, and exacerbated humero-ulnar subluxation in the other dog. Periosteal and interosseous ligament trauma, together with the location of the ulnar ostectomy, radial overstrain and radial hypertrophy were considered to be important factors in the pathogenesis of synostosis formation in these cases.Radio-ulnar synostosis was a complication of mid-diaphyseal ulnar ostectomy in two young dogs.
Keywords: Synostosis; ostectomy